Mandibular Reconstruction with Scapular Systems: A Single-Center Case Series Involving 208 Flaps. Issue 3 (9th August 2021) - Harada, Hiroyuki; Shimamoto, Hiroaki; Oikawa, Yu; Kuroshima, Takeshi; Tomioka, Hirofumi; Hirai, Hideaki; Tsushima, Fumihiko; Michi, Yasuyuki
Abstract : Background: The scapular flap is the most versatile composite flap used for mandibular reconstruction. The purpose of this study was to review and summarize findings of cases of mandibular reconstruction with a scapular flap and describe associated outcomes and complications. Methods: A total of 208 microvascular scapular free flaps were performed for mandibular reconstruction in a total of 205 patients from 2003 to 2018. This study involved a retrospective review of all eligible patients' medical records. Results: There were seven cases (3.4 percent) of microvascular thrombosis. Postoperative bone union was achieved by 201 patients, except for five with total flap necrosis and two with partial flap necrosis. There were four cases (1.9 percent) of mandibular condyle dislocation. Two major types of complications were observed at the donor site, including four cases of infection and six cases of scapular body fracture. Postoperative denture prosthesis was introduced to 97 patients (47.3 percent). Implant treatment was performed in 10 patients (4.9 percent). Functional and aesthetic outcomes were good to excellent. Conclusions: The scapular composite free flap for mandibular reconstruction was associated with favorable outcomes and demonstrated satisfactory results. Although scapular bone fracture is rare, patients who have undergone mandibular reconstruction using a scapular flap should be monitored for its presence.  CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.